INTERIOR DECORATIVE ARTS USED IN MEDIEVAL MADRASAHS (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
The article analyzes the decorative arts used in the interior of medieval madrasas in Central Asia, including ganch carving, wall painting, tilework, wood carving, muqarnas, calligraphy, and vegetal (floral) ornamentation. Their aesthetic, functional, and symbolic significance is examined. The study also highlights the distinctive interior features characteristic of the architectural schools of Samarkand, Bukhara, Khiva, and Tashkent.
Keywords: Ganch carving, wall painting, tilework, wood carving, muqarnas, calligraphy, vegetal ornaments.